A novel UBE2A splice site variant causing intellectual disability type Nascimento. Issue 7 (11th July 2022) - Yan, Shuyuan; Wang, Yanling; Chen, Ying; Yuan, Hongxia; Kuang, Xiaoni; Hou, Da; Li, Xueyi; Pan, Linglin; Huang, Guangwen; He, Jun; Wang, Tuanmei; Peng, Xiangwen
Abstract: X‐linked intellectual disability type Nascimento (XLID) is a rare disease caused by variants in the ubiquitin‐conjugating enzyme E2A gene (UBE2A). Patients with XLID have similar phenotypes, including speech impairments, severe intellectual disability, hearing loss, wide facies, synophrys, generalized hirsutism, and urogenital abnormalities. Till date, only two splice‐site variants of the UBE2A gene have been observed in patients with X‐linked ID type Nascimento. Here, we report the case of a Chinese boy with a syndrome clinically similar to XLID with speech impairment, severe intellectual disability, and moderate hearing loss. However, different characteristics were also present in the patient, including an inability to maintain his head in an upright posture. Both of the patient's palms have a single transverse palmar crease. Subsequent whole‐exome sequencing revealed a novel splice site variant in UBE2A (c.241 + 1 G > A). Our study not only expands the variant spectrum and clinical characteristics of UBE2A deficiency syndrome but also provides clinical evidence for genetic diagnoses. Abstract : Here, we report the case of a boy with a novel splice site variant in UBE2A. In addition to intellectual disability, we found novel characteristics, such as bone growth retardation in the fetus. Cardiac malformations were found in the fetal and neonatal period but disappeared as the patient grew older.